INVOLVING CHILDREN WITH SPECIAL NEEDS IN INCLUSIVE EDUCATION – A PROBLEM OF SPECIAL PEDAGOGICAL RESEARCH - Sulaymanova Muhlisa Kozimjon qizi; PhD Umida Mexmanovna Utbasarova (Web of Journals Publishing, 2025)
This article examines the pedagogical, psychological, and social aspects of involving children with special needs in inclusive education. It analyzes the theoretical foundations of inclusive education, the problems encountered in practice, and the ways to overcome them. The paper also presents recommendations aimed at expanding the opportunities for children with special needs to study in general educational institutions.
Keywords: Inclusive education, children with special needs, special pedagogy, educational integration, correctional support, psychological and pedagogical assistance.